A new purification method for 2-mercaptobenzothiazole and its application as vulcanization accelerator. (1st April 2023) - Shen, Yuhong; Jing, Xianhong; Mu, Xueliang; Dou, Jinpeng; Zhang, Qingwei; Zhang, Yidong; Liu, Yanjun; Li, Zhenqiu
Abstract: In this work, a new purification method for 2-Mercaptobenzothiazole (MBT) and its application as a vulcanization accelerator was reported, and the properties of MBT samples were comprehensively investigated. According to the chemical equation of this purified reaction, the byproduct of the CO2 method was easy to treat. Results showed that the melting point and yield of experimental CAMBT samples were increased to 173.6 °C and 93.11%, respectively. The chemical structure and crystal absorption peak of all MBT samples were also measured by the FTIR and XRD analysis. Thermogravimetric analysis was used to study the residue of resin in MBT samples. Element content confirmed the existence of C, N, H, and S elements, and there were no other elements in the products. What is more important, the mechanical properties of experimental CDMBT@NR and SAMBT@NR samples were better than that of UMBT@NR. Thus, this paper offers a new purification method for MBT and investigates its application as a vulcanization accelerator.